Answer:
Its a
Step-by-step explanation:
A integer is like a whole number by it self
answer for this question is 2 is to 4 is to6 is to 7
Umm, I think it is the first one.
Answer
-3
Step-by-step explanation:
x=4
4-5=-1
x=3
3-6=-2
-1+-2=-3
Answer:
(x-6) (2x+1)
Step-by-step explanation:
1) move everything over to the left side, so subtract 11x and 6.
2x^2 -11x - 6 = 0
2)multiply 2(a term) with -6 (c term)
x^2 -11x -12
3) factor and find what multiples to -12 and adds up to -11. in this case its -12 and positive 1
(x-12) (x+1)
4) divide -12 and 1 by the original a term (2)
(x-6) (x+1/2)
5) move the denominator of 2 over to the x.
(x-6) (2x+1)